Investigation of the material fragmentation model with the uniform scale subdivision energy distribution - Brodskii, R.E.; Virchenko, Yu.P. (Functional Materials, 2006)
Using the probabilistic Kolmogorov approach for the description of the material fragmentation process, it is shown that in the typical physical situation when the intensity energy inflow in the system is constant the Kolmogorov equation must be temporally inhomogeneous. In this case, for the special model with the uniform scale energy distribution expended for the subdivision, the limit Kolmogorov distribution law for fragment sizes is proved.